녹내장 환자에서 망막전위도의 ON-OFF 반응 소견 - 박가희; Ka Hee Park; 장지호; Ji Ho Chang; 박태관; Tae Kwan Park; 온영훈; Young Hoon Ohn (Daihan angwa haghoi jabji, 2012)
목적: 녹내장안에서 망막전위도의 ON-OFF 반응에 대해 알아보고자 한다. 대상과 방법: 녹내장군 22안, 녹내장의증군 13안, 정상군 15안을 대상으로 망막전위도 ON-OFF반응을 시행하여 a, b, d, i, Photopic negative response (PhNR) 파형의 진폭과 반응도달시간을 비교해보고, 망막신경섬유층 두께와의 상관관계를 알아보았다. 결과: 녹내장군, 녹내장의증군, 정상군에서 PhNROFF 진폭(uV)은 19.05 ± 11.41, 14.24 ± 10.37, 2.69 ± 12.16로 각 군 간 유의한 차이가 있었고(p＜0.01), PhNRON 진폭(uV)은 20.15 ± 13.99, 31.49 ± 17.09, 37.59 ± 9.53로 세 군 간 유의한 차이는 있으나(p＜0.01) 각군 간 차이를 보이지는 않았다. ON-OFF 반응의 PhNR 진폭은 망막신경섬유층 두께와 상관관계를 보였고(r=0.481, r=-0.480), Areas under the receiver operating characteristic curve는 0.782, 0.718이었다. 결론: ON-OFF 반응의 PhNR 진폭은 녹내장안을 구분하는 데 있어 진단적 가치를 지니고 있다. Purpose: To investigate whether there is a difference in ON- and OFF-responses of the photopic electroretinogram (ERG) in glaucomatous eyes. Methods: Photopic ERG and optical coherence tomography were performed in 15 normal, 13 glaucoma suspect, and 22 glaucoma subjects. Amplitudes and implicit times for a, b, d, i, photopic negative response (PhNR), and retinal nerve fiber layer thickness were compared among the three groups. Results: The PhNROFF amplitude (uV) was 19.05 ± 11.41 in the glaucoma group, 14.24 ± 10.37 in the glaucoma suspect group, and 2.69 ± 12.16 in the normal group, demonstrating a significant difference among the three groups (p < 0.01). The PhNRON amplitude (uV) was 20.15 ± 13.99 in the glaucoma group, 31.49 ± 17.09 in the glaucoma suspect group, and 37.59 ± 9.53 in the normal group, a significant difference (p < 0.01). However, there was no significant difference between the three groups. The ON-OFF response PhNR amplitude was correlated with retinal nerve fiber thickness (r = 0.481, r = -0.480, respectively), and areas under the receiver operating characteristic curve were 0.782, and 0.718, respectively. Conclusions: There is a potential role for the ON-OFF response PhNR in early detection of glaucomatous damage.